Separation, Weak Exogeneity and P-T Decomposition in Cointegrated VAR Systems with Common Features - Alain Hecq; Franz Palm; Jean-Pierre Urbain (Center for Economic Studies and ifo Institute (CESifo), 2002)
The aim of this paper is to study the concept of separability in multiple nonstationary time series displaying both common stochastic trends and common stochastic cycles. When modeling the dynamics of multiple time series for a panel of several entities such as countries, sectors, firms, imposing some form of separability and commonalities is often required to restrict the dimension of the parameter space. For this purpose we introduce the concept of common feature separation and investigate the relationships between separation in cointegration and separation in serial correlation common features. Loosely speaking we investigate whether a set of time series can be partitioned into subsets such that there are serial correlation common features in the sub-groups and that there do not exist linear combinations of the common cycles which are white noise. The paper investigates three issues. First, it provides conditions for separating joint cointegrating vectors into marginal cointegrating vectors as well as separating joint short-term dynamics into marginal short-term dynamics. Second, conditions for making permanent-transitory decompositions based on marginal systems are given. Third, issues of weak exogeneity are considered. Likelihood ratio type tests for the different hypotheses under study are proposed. An empirical analysis of the link between economic fluctuations in the U.S. and Canada shows the practical relevance of the approach proposed in this paper.
Keywords: 330; separation; cointegration; common features; weak exogeneity; P-T decomposition; consumption function